The Effectiveness of Project-Based Collaborative Learning in Improving English Speaking Skills of High School Students - Andi Suwarni; Nurasia Natsir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to evaluate the effectiveness of project-based collaborative learning in improving the English speaking skills of high school students. Using a quasi-experimental design, this study involved 64 eleventh-grade students divided into an experimental group (n=32) using project-based collaborative learning methods and a control group (n=32) using conventional methods. Data were collected through pre-test and post-test speaking assessments, classroom observations, and interviews with students and teachers. The results showed that the experimental group experienced a significant improvement in English speaking skills compared to the control group (p<0.05) with a large effect size (d=0.87). Qualitative analysis revealed that project-based collaborative learning increased students' motivation, confidence, and critical thinking abilities. These findings indicate that the project-based collaborative learning approach can be an effective strategy for developing English speaking skills in the EFL (English as a Foreign Language) context.